LSD: link strength based discovery protocol for dynamic ad hoc networks. (5th April 2010) - Bassem, Christine; El-Nahas, Amal
Service discovery is one of the main enabling gears for ubiquitous computing where people and computational devices embedded in the surroundings invisibly interact and share services. Such services, either hardware like printers and fax machines, or software like files and drivers, need to be discovered and invoked with minimum user intervention. This is the role of service discovery protocols. In this paper, we propose a fully distributed, energy efficient service discovery protocol for highly dynamic ad hoc environment. The proposed protocol opts for saving device energy and delay by selecting the most stable routes to the service providers. The protocol is evaluated through simulation experiments. Results showed a significant improvement in terms of saving the power capacity of the devices in the network and minimising the delay and the failure rate of service requests.